Development of indium tin oxide film texture during DC magnetron sputtering deposition - Jung, YS; Lee, SS (ELSEVIER, 2003)
The indium tin oxide (ITO) film texture development process during sputtering deposition was explored. Cross-section TEM images revealed that prepared ITO films have columnar structures. theta - 2theta X-ray diffraction (XRD) studies on ITO thin films deposited under various sputtering conditions were conducted. The change of XRD profiles with increasing thickness was monitored to elucidate the mechanism of film texture development. ITO films, which were deposited under conventional conditions, evolved to (400) orientation with increasing film thickness. In contrast, surplus amounts of additional oxygen gas flow suppressed growth of (400)-oriented grains. Meanwhile, moderate ranges of pressure and power density and higher substrate temperatures resulted in more (400)-oriented film textures. The development of texture to (400) orientation is attributed to a lower surface energy and a height advantage combined with shadowing effect. The ITO film growth process was assumed to be composed of two steps, the nucleatiom step and the evolution step. Higher adatom mobility is thought to be very important for the nucleation of (400)-oriented grains. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: PREFERRED ORIENTATION; STRUCTURAL-PROPERTIES; GROWTH